Dual output DC-DC quasi impedance source converter - Muhammad Ado; Awang Jusoh; Tole Sutikno; Mohd Hanipah Muda; Zeeshan Ahmad Arfeen (Institute of Advanced Engineering and Science, 2020)
A double output port DC-DC quasi impedance source converter (q-ZSC) is proposed. Each of the outputs has a different voltage gain. One of the outputs is capable of bidirectional (four-quadrant) operation by only varying the duty ratio. The second output has the gain of traditional two-switch buck-boost converter. Operation of the converter was verified by simulating its responses for different input voltages and duty ratios using MATLAB SIMULINK software. Its average steady-state output current and voltage values were determined and used to determine the ripples that existed. These ripples are less than 5% of the average steady-state values for all the input voltage and duty ratio ranges considered.